Análisis comparado de procesos de descentralización urbana: los casos de Barcelona y Buenos Aires - González, Giselle (El Colegio de México A.C., 2021)
Public territorialization policies between Buenos Aires and Barcelona are described and compared. From a qualitative design, the work is close to experiences in which processes of consolidation of public policies of territorial regionalization are observed, especially analyzing the consolidation process and the problems they currently present. The research is approached from three specific axes: context conditions, policies and actors. From there the power relations between different actors are investigated, the way in which political actors are constituted and the degrees of influence in the decision-making processes in each city. From the comparison it appears that the initiatives in Buenos Aires are designed from multilevel logics but their implementation shows strong centralization features in the central power. While in the case of Barcelona, multilevel designs and a distribution of reticular power that brings it closer to a cooperative model of metropolitan governance are embodied.